Analysis of Nurses' Fatigue and Stress Factors in the COVID-19 Isolation Room in Indonesia: A Cross-Sectional Research - Nila Sari; Roxsana Devi Tumanggor (Caring: Indonesian Journal of Nursing Science, 2023)
The COVID-19 pandemic has increased workloads and psychologically affected the nurses due to a long time of exposure to the virus, and causes a decrease in energy, leading to stress and fatigue. This study aims to analyze the factors associated with fatigue and stress experienced by nurses in the COVID-19 isolation room in Indonesia.  This study involved 50 nurses who worked in the hospital's COVID-19 isolation room. The instrument used consists of three parts, namely the demographic data, a Fatigue Scale-14 questionnaire, and a Perceived Stress Scale-10. The results of the validity and reliability tests carried out on both instruments were declared valid and reliable. The data were collected by providing questionnaire link in form of a google form link through WhatsApp to each research sample. Subsequently, the collected data were analyzed using cross-tabulation analysis and chi-square test.  Results showed that the majority of respondents were aged 31-40 years and most were female (35%). A total of 64% experienced moderate fatigue and 82% of nurses were in the moderate stress category. Based on the fatigue data tabulation analysis, there is no relationship between demographic data variables and fatigue. However, there is a relationship between work duration and stress variables as well as fatigue and stress experienced by nurses.  These results showed that the stress and fatigue experienced by COVID-19 nurses are related to the nurses’s certain characteristics that have the potential to worsen mental health conditions.  It Is recommended to explore more related to fatique factors in the future with specific nursing interventions.